Afamin as an Independent Diagnostic Marker of Gestational Diabetes Mellitu - Asghar, Jawaria; Naeem, Uzma; Bibi, Afshan; Khan, Qamar ud din; Sajjad, Zunnera; Irfan, Rafia (Pakistan Armed Forces Medical Journal, 2025)
Objectives: To assess utility of afamin (AFM) as an independent marker of Gestational Diabetes Mellitus (GDM) in comparison with Oral Glucose Tolerances Test (OGTT), and to determine cut off value for afamin.Study Design: Diagnostic accuracy study.Place and Duration of Study: Chemical Pathology and Gynecology Department, Army Medical College and Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jan to Dec 2021.Methodology: Ninety-six pregnant females with history of 24 to 28 weeks of gestation were included in this study, out of which 48 were cases of GDM (Group-A) and 48 were included in age and gestation matched control group (Group-B). Fasting plasma glucose was taken for 75g OGTT and Afamin (AFM) levels. AFM concentrations were compared with OGTT results between the two groups.Results: Median age of cases was 30.0(3.0) years and of controls was 29.5(5.0) years. A significant difference was found in the median values of serum afamin, fasting plasma glucose and 1- and 2-hours plasma glucose post-glucose load between Group-A and Group-B. The optimal cut off level of serum afamin for diagnosing GDM was determined as 71.2 mg/L, with Area Under Curve (AUC) 0.993, sensitivity 97.9% and specificity 79.0%.  AUC for serum afamin levels was greater than HbA1c, fasting plasma glucose and 1-hour plasma glucose post-glucose load.Conclusion: Median second trimester serum afamin levels were significantly higher in Group-A as compared to Group-B, making it a reliable test for GDM in second trimester.